Standing figures of Sursundaris on the Pillars - Temples of India Project Team (Jio Institute, 2024)
The shafts of the front pillars are adorned with loops of bells and hanging bells. The pillars are adorned with the graceful standing figures of sursundaris (celestial maidens) which are currently broken and damaged. The figural panel at the top of the cushion abacus depicts sursundaris, dancers, and couples.